SÍNDROME DE BART: RELATO DE CASO E REVISÃO - Maria Paula Sandri Facchin; Mayara Reis de Oliveira; Mauren Seidl; Marina Helena Capra; Ana Carolina Vieira; Fabiana Rubbo de Melo; Jaqueline Reginatti (Sociedade Brasileira de Pediatria, 2023)
MAB, newborn male, e.t , gestational age of 37 weeks and 5 days. During his initial care, no changes were noted, except for skin lesions: cutaneous aplasia on limbs, back, inguinal region and mucous membranes, as well as bullous lesions and nail alterations. The e.t o nt the anatomopathological exam was epidermolysis bullosa. The patient had a bad e.t o nt and developed neonatal sepsis, and several antibiotic therapy and dressings were performed. After presenting n e.t o ntent clinical worsening and refractoriness to the proposed treatment, he died at 57 days of life. Barts syndrome is a genetic condition, and its diagnosis is clinical, made through the triad: cutaneous aplasia, epidermolysis bullosa and nail dystrophies. This syndrome is linked to autosomal dominant inheritance and occur e.t oto a mutation in the type VII collagen gene. Despite having a good prognosis, its diagnosis must be early, so the treatment, which is based on topical dressings and antibiotics, can be started as soon as possible to prevent possible complications such as: sepsis, hemorrhages, hydroelectrolytic disorder and death.